The Prognostic Model and Drug Sensitivity of LKB1-Mutant Lung Adenocarcinoma Based on Immune Landscape - Wang, Guanghui; Zheng, Haotian; Zhao, Xiaogang; Wang, Yadong; Zeng, Yukai; Du, Jiajun (Frontiers in Molecular Biosciences, 2022)
Background: Lung cancer is the most common cause of cancer-related deaths worldwide. LKB1-mutant lung adenocarcinoma (LUAD) is a unique subtype of this deadly cancer. LKB1 mutations cause functional changes in a variety of cell processes, including immune functions, that affect prognosis. To date, the potential role of immunity in the prognosis of LKB1-mutant LUAD is not well understood. Methods: We systematically analyzed immune-related genes in LUAD samples from The Cancer Genome Atlas (TCGA) database. ESTIMATE and CIBERSORT algorithms were used to explore the immune microenvironment. A prognostic risk model was constructed, and prognostic, immune function, drug sensitivity, and model specificity analyses were performed to identify the effectiveness of the model. Results: Our results showed that LKB1 mutations suppressed immune function in LUAD. A three-gene signature was constructed to stratify patients into two risk groups. The risk score was an independent predictor for overall survival (OS) in multivariate Cox regression analyses [hazard ratio (HR) > 1, p = 0.002]. Receiver operating characteristic (ROC) curve analyses confirmed that the risk score has better performance than clinicopathological characteristics. Functional analysis revealed that the immune status was different between the risk groups. ZM.447439 was an appropriate treatment for the high-risk group of patients. This risk model is only suitable for LKB1-mutant tumors; it performed poorly in LUAD patients with wild-type LKB1. Conclusion: Our findings indicate the potential role of immunity in LKB1-mutant LUAD, providing novel insights into prognosis and guiding effective immunotherapy.